HUBUNGAN INTAKE CAIRAN DENGAN TEKANAN DARAH PADA KLIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RUANGAN HEMODIALISA RSUD M NATSIR KOTA SOLOK TAHUN 2021 - Kurniati Maya Sari; Nabila Mutiara (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Hemodialysis is the process of exchanging solutes and body waste products. Residual substances that accumulate in CRF patients are removed by a passive diffusion mechanism of a semi-permeable membrane. Based on a preliminary study conducted by researchers on September 12, 2021 at M. Natsir Hospital, data from interviews and observations of 10 chronic kidney failure patients found 6 people with increased body weight and 4 people with normal weight. However, there were also 7 patients with increased blood pressure and 3 normal blood pressure. This is what causes patients to often experience increased blood pressure and severe IDWG which can cause edema and dizziness before carrying out hemodialysis. The purpose of this study was to determine the relationship between fluid intake and blood pressure in clients with chronic kidney failure undergoing hemodialysis in the hemodialysis room at M Natsir Hospital. This type of research is analytic through a cross-sectional approach. The population in this study were all Chronic Kidney Failure patients undergoing hemodialysis in the Hemodialysis room of RSUD M Natsir, namely there were 45 patients using accidental sampling technique. Data is collected by interviewing and observing. After that, the data were analyzed using univariate and bivariate and computerized processing using the chi square test. The results of the study showed that there was a significant relationship between fluid intake and blood pressure in clients with chronic kidney failure with p value = = 0.029 and OR = 6.107. Based on the research results, it is hoped that health workers, especially nurses working in special rooms, can provide education on how to limit fluid intake and group blood pressure in patients with chronic kidney failure who carry out routine hemodialysis care. Keywords: Fluid Intake, Hemodalisa